Multicentre study on pulmonary arterial hypertension therapies in fontan patients: underutilised or of limited use?. (25th November 2020) - Constantine, A; Jenkins, P; Oliver, J; Chung, N; Jansen, K; Fitzsimmons, S; Walker, N; Papaioannou, V; Parry, H; Condliffe, R; Tulloh, R; Dimopoulos, K; et al.
Abstract: Introduction: The Fontan circulation is successful in abolishing cyanosis and chronic volume overload in congenital heart disease (CHD) patients with single ventricle physiology. "Fontan failure" is a major cause of poor quality of life and mortality in these patients. Recently, pulmonary arterial hypertension (PAH) therapies have been used in Fontan patients with variable success, even though patients included in these studies are generally at the best end of the spectrum. Aim: To assess contemporary patterns of PAH therapy in Fontan patients in large specialist CHD centres. Methods: We identified all adult patients with a Fontan-type circulation under active follow-up in 8 specialist CHD centres between 2009 and 2019. Patients on PAH therapies were matched by age and gender to untreated patients (1:1 or 1:2). Baseline data were collated immediately prior to initiation of therapy (treated group) or from a synchronous routine clinical assessment (untreated group). Results: During the study period, 70 Fontan patients were started on PAH therapy (6.5% of those under follow-up). The majority 63 (90.0%) were started on monotherapy with a phosphodiesterase-5 (PDE5) inhibitor, 6 (8.6%) patients were started on an endothelin receptor antagonist (ERA) and 1 (1.4%) received early sequential therapy with a PDE5 inhibitor and ERA. Prostacyclin analogues were not used, and no patients received triple therapy. Overall, 51 (72.9%) patients started therapy electively (49% in outpatient clinic, 51% as day case admission), while 18 (25.7%) were treated following urgent hospital admission with fluid overload +/− acute kidney injury. The remainder (2, 2.9%) started therapy following cardiac surgery. Adverse events during treatment were rare. Patients starting PAH therapy were matched to 112 untreated patients (table 1). Patients were well matched between groups for age (p=0.52) and sex (p=0.27). Treated patients were more likely to be significantly impaired than matched patients (56.7% vs. 8.6% in NYHA class III/IV, p<0.0001) and were more likely to have ascites (16.2% vs. 0.9%, p=0.0002). Treated patients were also more likely to have a lower albumin level (43 [14–56] vs. 45 [29–54], p=0.01) or to be on a loop diuretic e.g. furosemide (p<0.0001), at a higher daily dose (p<0.0001) than matched patients. Only a quarter of patients on therapies had no high-risk features (24.2%), 80% of whom were from a single centre. Conclusion: A small minority of Fontan patients followed in specialist centres receive PAH therapies. PAH therapy was reserved in most centres for patients with more advanced disease, targeting predominantly those with a "failing Fontan" in an individualised approach, in line with the recent adult CHD American Heart Association (AHA) guidelines. Further studied are needed to establish the role of PAH therapies in Fontan patients, provided that adult patients with advanced disease who are at increased risk of adverse outcome are included. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Dr Constantine received an educational grant from Actelion Pharmaceuticals, a Janssen company of Johnson & Johnson, which helped to pay for travel for data collection.